Toxicidade aguda e risco ambiental do antibiótico oxitetraciclina para tilápia (Oreochromis niloticus), Daphnia magna e Lemna minor - Machado, A. A. [UNESP]; Américo-Pinheiro, J. H P [UNESP]; Carraschi, S. P. [UNESP]; Cruz, C. [UNESP]; Machado-Neto, J. G. [UNESP] (FapUNIFESP (SciELO), 2016)
The aim of this study was to classify the antibiotic Terramycin® according to acute toxicity and the environmental risk that it poses for Oreochromis niloticus, Daphnia magna, and Lemna minor based on its active ingredient oxytetracycline (OTC). In addition, the occurrence of acute poisoning signs in fish and antibiotic dilution effect in the water quality variables were observed. For this purpose, fingerlings, neonates, and while were exposed to the concentrations of OTC. According to OTC acute toxicity test results, the Terramycin® was classified by acute toxicity and environmental poisoning risk classes. To O. niloticus, the calculated LC(I)50;48h was 6.92 mg L-1, for D. magna the EC(I)50;48h was 0.17 mg L-1, while for L. minor, IC(I)50;7d was 0.68 mg L-1. Terramycin® was classified as very toxic to O. niloticus, and highly toxic to D. magna and L. minor and cause risk of environmental poisoning for the three organismis tested. Concentrations of 7.5 and 8.0 mg L-1 OTC reduce the concentration of dissolved oxygen in the water. According to this study, Terramycin® should not be used in aquaculture, as it is highly toxic and causes risk of environmental toxicity test organisms.
Acute toxicity and environmental risk of oxytetracycline antibiotc for tilapia (Oreochromis niloticus), Daphnia magna, and Lemna minor
Keywords: Antibiotic; Aquatic organisms; Ecotoxicity; Fish; Macrophyte